Hak Kewarganegaraan dan Kebijakan Pemerintah: Evaluasi Peraturan Perundang-Undangan di Indonesia - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; A’izzatul Ifada; Bagas Eka Syahputra; Meylin Yunda Safira (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
This research evaluates the effectiveness of citizenship legislation in Indonesia, focusing on Law No. 12 of 2006. The background of this study is based on the importance of protecting citizenship rights within the context of evolving social and political dynamics. The aim of the research is to identify discrepancies between regulations and practices, as well as to analyze the impact of policies on social integration and the protection of individual rights. The methodology employed is normative legal analysis, which includes legislative, conceptual, and comparative approaches, along with data collection through literature review and interviews with legal experts. The findings indicate that although Law No. 12 of 2006 has brought positive changes, the implementation of policies still faces challenges such as inconsistency and administrative obstacles. The implications of this research highlight the need for reforms in citizenship policy that are fairer and more responsive, which can enhance the protection of individual rights and create a more inclusive system for all citizens.